Analyzing NSAIDS research trends: a six-year bibliometric study (2018-2023) on directions, themes, and dimensions - Alhatim, Husein; Alshadfan, Hisham; Omar Fauzee, Mohd Sofian; Zakaria, Zainul Amiruddin; Hakim, Muhammad Nazrul (Malque Publishing, 2026)
The commonly used class of pharmaceuticals known as nonsteroidal anti-inflammatory drugs (NSAIDs) has important effects on the treatment of pain and the decrease of inflammation. Medical progress and public health depend on an understanding of the patterns, areas of study, and effects of NSAIDs. To determine current research trends, this study uses Scopus to look up published articles on NSAIDs from 2018 to 2023. By emphasizing areas of increased interest and revealing gaps that could guide future study, bibliometric analysis allows us to get insights into the changing environment of NSAID research. With this strategy, new health issues are addressed, and the corpus of research is maintained to support educated medical practices. The most referenced articles, journal-related performance, trends in publishing and citation performance, and developing research cluster keywords were all analyzed in this study. The goals of the study were attained by using a bibliometric analysis that was directed by four research questions. Using Microsoft Excel, VOSviewer, and Harzing's Publish or Perish tools, the study first extracted information and examined keyword co-occurrence. To determine themes and dimensions from the keyword clusters found by VOSviewer, content analysis was also done. The findings revealed eleven new study term clusters on NSAIDS, such as: (a) 2020 had the highest number of NSAIDS citations, followed by 2019 and 2018. (b) In 2023, PLos One, Pharmaceutical, Chemosphere, and the Cochrane Database of Systematic Reviews published sixteen referenced journals on NSAIDS. (c) the top ten papers cited from 2018 to 2023, with 2020 having the most citations (782), (d) Ten clusters that emerged from the 42 NSAIDS-related titles, yielding ten dimensions (e.g., Optimized Pain Management; Therapeutic Expansion's Cardiovascular Safety; Changing Knowledge of NSAID Safety). As a result, suggestions are made for additional research to broaden and deepen this important area.